Pendekatan Mawḍu‘i terhadap Hadis-Hadis Eskatologi: Relevansi dan Implikasinya terhadap Penguatan Aqidah - Hadariyah; Siti Waspiatul Kamilah; Salim Rosyadi (Al-Hasyimi: Jurnal Ilmu Hadis, 2025)
The thematic approach in understanding hadith is to understand the meaning contained in the hadith by studying other hadiths related to the same topic of discussion and paying attention to the correlation of each so that a complete understanding is obtained. Eschatology in Islam includes discussions about the Day of Judgment, death, resurrection, the calculation of deeds, heaven, and hell, which are fundamental parts of the pillars of faith. However, the understanding of eschatological hadiths is often still partial and textual, so that their moral and spiritual messages have not been fully internalized in the lives of Muslims. This study aims to achieve strengthening of faith through the study of eschatological hadiths using the mawḍu‘i (thematic) approach. This study uses a qualitative approach with the application of the thematic hadith method. The formal object of this study is that the mawḍu‘i approach is able to offer solutions by studying all hadiths related to the theme of eschatology systematically and holistically. It can be concluded that in this study, the study of mawḍu‘i helps integrate theological and moral aspects in the eschatological hadith so that the aqidah formed is not only theoretical, but also applicable in the daily lives of Muslims. Thus, the mawḍu‘i approach is an effective method that can strengthen beliefs and build strong faith characters amidst the dynamics of modern life. Therefore, the development of thematic hadith studies is highly recommended to support more meaningful and relevant Islamic education and preaching